PENGARUH PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN ASING TERHADAP PENGUNGKAPAN TANGGUNG JAW AB SOSIAL PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Anggono, Ricky Ivan; Handoko, Jesica (Jurnal Akuntansi Kontemporer, 2009)
Corporate social disclosures are needed to communicate social and environmental effects derived from corporate's economic activities to stakeholders, to the interested parties. The degree of disclosure is affected by several factors, internally and or externally. The purpose of this research is focused on internal factors: profit and stock ownership. Profitability and stock ownership are predicted influence the degree of corporate social disclosure in mining companies. listed at Indonesian S'ock Exchange in 2005-2007, Intention of this research is to know 'whether profitability, institutional ownership and foreign ownership influence to level of corporate social disclosure. Corporate social disclosure done by companies in several areas of energy, health and safety at work, labor, product ana social activities, This research applies company size as control variable. Nine mining companies selected with purposive sampling technique. Data analyzed llSlng linear regression and showed only profitability variable and foreign o',j/nership influenced corporate social disclosure significantly.